2000
DOI: 10.1021/jf9911186
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Formation of Di-d-fructose Dianhydrides during Thermal Treatment of Inulin

Abstract: Thermal treatments of solid mixtures of inulin and citric acid result in the formation of di-D-fructose dianhydrides and oligomers derived therefrom. The kinetics of formation of these compounds have been investigated and simulated in computer studies. A mechanism is proposed. The conditions used in this study were analogous to the conditions pertaining to the roasting of chicory, during which similar compounds are formed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 22 publications
2
33
1
Order By: Relevance
“…Earlier studies showed that DFAs could be produced during the chemical hydrolysis of inulin by dilute acid to produce fructose (Jackson and Goergen 1929;McDonald 1946). Then, many references reported that DFAs were formed by nonenzymatic catalysis of fructose and fructose-containing compounds such as sucrose, FOS, and fructans, especially under high temperature and acidic conditions (Christian et al 2000;Manley-Harris and Richards 1996;Ratsimba et al 1999;Trabs et al 2011). And DFAs were approved to be easily generated by caramelization of these raw materials during food processing (Defaye and Garcia Fernandez 1994;Kuhnert 2012, 2013;Rhourrhi-Frih et al 2012).…”
Section: Existence Of Dfas In Naturementioning
confidence: 99%
“…Earlier studies showed that DFAs could be produced during the chemical hydrolysis of inulin by dilute acid to produce fructose (Jackson and Goergen 1929;McDonald 1946). Then, many references reported that DFAs were formed by nonenzymatic catalysis of fructose and fructose-containing compounds such as sucrose, FOS, and fructans, especially under high temperature and acidic conditions (Christian et al 2000;Manley-Harris and Richards 1996;Ratsimba et al 1999;Trabs et al 2011). And DFAs were approved to be easily generated by caramelization of these raw materials during food processing (Defaye and Garcia Fernandez 1994;Kuhnert 2012, 2013;Rhourrhi-Frih et al 2012).…”
Section: Existence Of Dfas In Naturementioning
confidence: 99%
“…Furthermore, we had observed the formation of low-molecular degradation products which were cleavable by acid to fructose (Boehm et al 2005). Inspired by studies of Christian and Manley-Harris (2000), the aim of the present study was to identify degradation products formed during a dry heating of inulin.…”
Section: Introductionmentioning
confidence: 99%
“…2) while a total hydrolysis had been obtained on the blue agave WSC pool. Various works have reported the formation of di-D-fructose dianhydrides resulting from the thermal degradation of inulin, (Blize, Manley-Harris, & Richards, 1994;Bohm, Kaiser, Trebstein, & Henle, 2005;Christian, Manley-Harris, Field, & Parker, 2000;Manley-Harris & Richards, 1996). These compounds are cleavable by acid into two fructose monomers (Bohm et al, 2005).…”
Section: Discussionmentioning
confidence: 99%